Shugan Jieyu Capsule in Post-Stroke Depression Treatment: From Molecules to Systems - Zhang, Meng; Bai, Xue (Frontiers in Pharmacology, 2022)
Post-stroke depression (PSD) is the most common non-cognitive neuropsychiatric complication after stroke, and about a third of patients with stroke have depression. Although a great deal of effort has been made to treat PSD, the efficacy thereof has not been satisfactory, due to the complex pathological mechanism underlying PSD. In Traditional Chinese Medicine (TCM) theory, PSD is considered to be a combination of “stroke” and “Yu Zheng.” The holistic, multi-drug, and multi-objective nature of TCM is consistent with the treatment concept of systems medicine for PSD. TCM has a very long history of being used to treat depression, and various TCM prescriptions have been clinically proven to be effective in improving depression. Among the numerous prescriptions for treating depression, Shugan Jieyu capsule (SG) is one of the classic prescriptions. Additionally, clinical studies have increasingly confirmed that using SG alone or in combination with Western medicine can significantly improve the psychiatric symptoms of PSD patients. Here, we reviewed the mechanism of antidepressant action of SG and its targets in PSD pathologic systems. This review provides further insights into the pharmacological mechanism, drug interaction, and clinical application of TCM prescriptions, as well as a basis for the development of new drugs to treat PSD.